UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI-NILAI TASAMUH DI SMP ISLAM MA’ARIF 02 KOTA MALANG - Erinda Nurtaviana Arum (VICRATINA, 2019)
This study aims to determine the teacher's efforts in instilling the values of tasamuh attitudes. This research was conducted at Ma'arif 02 Malang Islamic Middle School which began in May 2019. In this study we used data collection methods, field observations, interviews and documentation. Methods of analyzing data by reducing data, presenting data, and drawing conclusions. In this analysis using descriptive which aims to explain the characteristics and aspects relevant to the phenomenon experienced. This research shows that students' values in behaving, students' values in opinion and students' values in culture. Planting the attitudes of tasamuh such as prayers in congregation, shaking hands with the teacher, commemorating the great day of Islam and planting 3S, namely Smile, Sapa, Salam.Kata Kunci : Upaya Guru PAI, Nilai Tasamuh